Radioimmunotherapy (RIT) for Follicular Lymphoma achieves long term lymphoma control in first line and at relapse: 8‐year follow‐up data of 281 patients from the international RIT‐registry. (4th December 2018) - Hohloch, Karin; Windemuth‐Kieselbach, Christiane; Kolz, Julia; Zinzani, Pier Luigi; Cacchione, Roberto; Jurczak, Woijciech; Bischof Delaloye, Angelika; Trümper, Lorenz; Scholz, Christian W.
Summary: To assess efficacy of radioimmunotherapy (RIT) in follicular lymphoma, data from 281 patients collected in the RIT Network, with a median follow‐up of 8·2 years after RIT were analysed. RIT was given at first line in 18·5% and at relapse in 81·5%. Following first line therapy, 76·9% achieved complete remission (CR), 9·6% partial remission (PR), 1·9% stable disease (SD) and 1·9% had progressive disease (PD); response was not documented in 9·7%. At relapse, the rate of CR was 48·5% and that of PR was 16·6%, SD 2·6% and PD 10·5%; response was not documented in 21·8%. After median follow‐up of 8·2 years, median progression‐free survival (PFS) for all was 2·54 years, median overall survival (OS) was not reached. Median PFS and OS (both not reached) were significantly better in first line, compared to RIT at relapse (PFS, 2·11 years; OS, 10·8 years; P  = 0·0037 and P  = 0·0021, respectively). Overall 8‐year PFS was 33·9%, 53·6% for first line and 29·6% for relapsed individuals. Overall 8‐year OS was 58·8%, 78·1% for first line and 54·5% for relapsed patients. Thirty‐five patients (12·5%) developed secondary malignancy and 16 patients (5·7%) experienced transformation into aggressive lymphoma. RIT is a safe and effective treatment option for follicular lymphoma, both at front line and relapse with an 8‐year PFS of 53·6% and 29·6%, respectively.